2016
DOI: 10.15171/ijhpm.2016.65
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Healthcare Utilisation and Out-of-Pocket Payments in the Context of Free Public Primary Healthcare in Zambia

Abstract: Background: Access to appropriate and affordable healthcare is needed to achieve better health outcomes in Africa. However, access to healthcare remains low, especially among the poor. In Zambia, poor access exists despite the policy by the government to remove user fees in all primary healthcare facilities in the public sector. The paper has two main objectives: (i) to examine the factors associated with healthcare choices among sick people, and (ii) to assess the determinants of the magnitude of out-of-pocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
63
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 36 publications
(53 reference statements)
15
63
2
Order By: Relevance
“…It is also not surprising and well aligned with existing literature that better‐educated individuals incurred higher OOPE. In addition to SES, education acts as an important enabling factor facilitating informed decision‐making when it comes to healthcare seeking . Grossman postulates that education also increases the efficiency of the investment made, hence suggesting that the money spent by educated people is probably better directed toward selection of the most appropriate treatment.…”
Section: Discussionsupporting
confidence: 88%
“…It is also not surprising and well aligned with existing literature that better‐educated individuals incurred higher OOPE. In addition to SES, education acts as an important enabling factor facilitating informed decision‐making when it comes to healthcare seeking . Grossman postulates that education also increases the efficiency of the investment made, hence suggesting that the money spent by educated people is probably better directed toward selection of the most appropriate treatment.…”
Section: Discussionsupporting
confidence: 88%
“…A study looking at the financial protection conferred by the free care policy found that 29.9% and 45% of patients in public rural and urban health centres respectively incurred some expenditures (Masiye et al, ). In a follow‐up study using the same data, Masiye and Kaonga () conclude that in 2014, “despite the removal of user fees in public primary healthcare in Zambia, access to healthcare is highly dependent on an individual's socio‐economic status, illness type and region of residence.” Together with our findings, this suggests that user fee removal may not necessarily be the silver bullet to move towards greater access for the poorer population and quicker move towards universal coverage. Evidence from several settings also point to the potential disruptive effects of free care policies on health systems (e.g., drug shortages, staff dissatisfaction, and insufficient funding) and therefore the need to prepare, plan, and introduce complementary measures to ensure a more positive outcome (Ridde, Robert, & Meessen, )…”
Section: Discussionmentioning
confidence: 99%
“…Third, the higher OOP expenditure burden in NHI than MA was identified over a 6-years trend from 2008 to 2013. OOP expenditure has been reported to have disadvantages that impede healthcare utilization when inevitably seek health care [35][36][37][38][39][40]. Therefore, NHI subjects with a severe disease such as ESRD have a greater financial burden than MA.…”
Section: Discussionmentioning
confidence: 99%